Démarche multidisciplinaire appliquée à l’analyse d’une activité dans un environnement dynamique : la conduite de véhicules légers à La Poste pour la distribution du courrier et des colis - Florence Hella; Anca Radauceanu; Jean-Jacques Atain-Kouadio; Raphaël Payet; Régis Colin (Perspectives Interdisciplinaires sur le Travail et la Santé)
A complex activity different from personal driving, professional light vehicle driving is becoming increasingly important in the delivery/messaging sector faced with new consumption patterns. Sparsely studied, health risks other than road accidents were approached in an exploratory multidisciplinary study conducted in collaboration with the La Poste group. Its objective was to explore, in work situation, the different components of the mail/parcel delivery activity, and particularly the driving activity as a structuring part of the distribution activity. The methodological approach combining ergonomic analyses and a medical approach has revealed postural and psychological constraints as well as complaints mainly related to the characteristics of the distribution rounds. These findings contributed to the construction of an epidemiological study aimed to analyze risk factors related to driving light vehicles for postal delivery activities.